The Effect of Workload Rewards and Organizational Commitment on Employee Performance Through Job Satisfaction as an Intervening Variable: Pengaruh Reward Beban Kerja dan Komitmen Organisasi terhadap Kinerja Karyawan Melalui Kepuasan Kerja sebagai Variabel Intervening - Cahyati, Inneke; Sumartik (Universitas Muhammadiyah Sidoarjo, 2022)
This study aims to determine the effect of reward (X1), workload (X2), and organizational commitment (X3) on employee performance (Y) through job satisfaction as an intervening variable (Z). This research has a causal concept with the aim of obtaining truth results whether proven or not through the formulated hypothesis and using data analysis. The analytical tool used in this research is path analysis technique with the help of SPSS (Statistical Package for the social science) version 25 for windows. The primary data in this study were obtained from a questionnaire whose measurement was using a Likert scale which was tested using validity and reliability tests. The results of this study show that (1) reward has a positive and significant effect on job satisfaction, (2) workload has a positive and significant effect on job satisfaction, (3) organizational commitment has a positive and significant effect on job satisfaction, (4) rewards have a positive effect and significant to employee performance, (5) workload has a positive and significant effect on employee performance, (6) organizational commitment has a positive and significant effect on employee performance, (7) job satisfaction has a positive and significant effect on employee performance, (8) reward has an effect positive and significant impact on employee performance through job satisfaction as an intervening variable, (9) workload has a positive and significant effect on employee performance through job satisfaction as an intervening variable, (10) organizational commitment has a positive and significant effect on employee performance through job satisfaction as an intervening variable.